KOMPETENSI MANAJERIAL KEPALA SEKOLAH MELALUI MODEL BLENDED LEARNING DALAM MOTIVASI BELAJAR SISWA PADA ERA NEW NORMAL COVID-19 - Badruzzaman; M Saroni (Pascasarjana Unviersitas Majalengka, 2021)
The Covid-19 pandemic has a wide impact on various aspects of social life including education. The learning process in the new normal era causes many problems for students, especially decreased learning motivation due to boredom. This study aims to identify and describe: a) the principal managerial competence in overcoming the decline in student motivation in the new normal era; b) Application of the blended learning model in the new normal era; and c) The development of student motivation at SMP Negeri 1 Jatiwangi in the new normal era after the blended learning model was applied. The research approach used qualitative by means of collecting in-depth interviews with informants who were determined purposively. The data obtained were analyzed descriptively interpretive through data reduction, data presentation, and drawing conclusions. The validity of the data was tested through triangulation techniques. The results showed: a) the principal managerial competence was included in the competent category; b) Application of the blended learning model, which is optional between face-to-face combination and face-to-offline combination; and c) After the blended learning model was applied, student motivation increased and boredom decreased. In conclusion, the principal's managerial competence through the application of blended learning can increase student motivation.